A glossary of mathematical terms : with illustrations and examples : a companion to mathematics - Τζελέπης, Γεώργιος Α. (Leader Books, 2001)
Are you preparing for College Entrance examinations? - Are you reviewing for your final exams in geometry, or algebra? - Are IB examinations coming up? - Do you need concise, understandable and helpful information? If so, then you will find that the present book may be just what you need to help you through.